Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd005632.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Steroid avoidance or withdrawal for kidney transplant recipients

Abstract: Background Steroid-sparing strategies have been attempted in recent decades to avoid morbidity from long-term steroid intake among kidney transplant recipients. Previous systematic reviews of steroid withdrawal after kidney transplantation have shown a significant increase in acute rejection. There are various protocols to withdraw steroids after kidney transplantation and their possible benefits or harms are subject to systematic review. This is an update of a review first published in 2009. Objectives To eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 205 publications
3
90
2
2
Order By: Relevance
“…10 Steroid cessation or avoidance has been associated with reduced cancer incidence, but this has not reached statistical significance in meta-analysis. 50 Regarding other immunosuppressive drugs, we found no association of CNIs with SCC development in this cohort. This is in contrast to the article by Dantal et al 51 in which low-dosage CNI regimens protected from SCC development within 5 years of transplantation.…”
Section: Cd28contrasting
confidence: 52%
“…10 Steroid cessation or avoidance has been associated with reduced cancer incidence, but this has not reached statistical significance in meta-analysis. 50 Regarding other immunosuppressive drugs, we found no association of CNIs with SCC development in this cohort. This is in contrast to the article by Dantal et al 51 in which low-dosage CNI regimens protected from SCC development within 5 years of transplantation.…”
Section: Cd28contrasting
confidence: 52%
“…Cardiovascular risk factors following renal transplant transplant diabetes was similar in all groups, although the number of RTRs who were able to be managed with diet alone was greater in those who had avoided steroids compared to those who were treated conventionally. This is supported by a Cochrane review of 30 RCTs which found that steroidsparing and withdrawal strategies showed benefits in reducing post-transplant diabetes requiring treatment and CV events [78] . They concluded that steroid avoidance and steroid withdrawal strategies in kidney transplantation are not associated with increased mortality or graft loss despite an increase in acute rejection.…”
Section: Diabetes Mellitusmentioning
confidence: 84%
“…Meta-analyses of randomized controlled trials of steroid withdrawal have demonstrated similar transplant outcomes despite an increased risk for acute rejection with early steroid withdrawal when compared to steroid maintenance. [8][9][10] A registry analysis by Luan and associates showed a reduced risk for graft failure and patient death at 1 and at 4 years in kidney transplant recipients continued on a steroid-free regimen. 11 The 5-year prospective randomized trial by Woodle and associates demonstrated reductions in weight gain, new onset of type 2 diabetes mellitus after transplant, and hypertriglyceridemia in kidney transplant recipients randomized to early steroid withdrawal following antibody induction and calcineurin inhibitor and mycophenolate mofetil maintenance.…”
Section: Discussionmentioning
confidence: 99%